2013
DOI: 10.1016/j.mito.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in selective mitochondrial association by direct modification of a mitochondrial targeting signal peptide on a liposomal based nanocarrier

Abstract: The focus of this study was on the development of a nano carrier targeted to mitochondria, a promising therapeutic drug target. We synthesized a lipid derivative that is conjugated with a mitochondrial targeting signal peptide (MTS), which permits the selective delivery of certain types of proteins to mitochondria.We then explored the use of an innovative technology in which MTS and the MITO-Porter were integrated.The latter is a liposome that delivers cargos to mitochondria via membrane fusion. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 37 publications
1
24
0
2
Order By: Relevance
“…The envelopes were composed of 1, 2-dioleoyl-sn- The modification of the MTS peptide resulted in a gradual increase in the diameter of the MITOPorter, and aggregation occurred when with MTS exceeded 2.5 mol% (Table S1). This tendency 4 corresponded to a previous report showing that it is difficult to maintain envelope-structures in the presence of high densities of the MTS peptide (12). To overcome this problem, we used 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-Mal-PEG (Mal-PEG-DSPE) (Nippon Oil and Fats Co.; Tokyo, Japan) as an anchor between the MTS-peptide and the envelopes of the MITO-Porter.…”
Section: Main Textsupporting
confidence: 90%
See 2 more Smart Citations
“…The envelopes were composed of 1, 2-dioleoyl-sn- The modification of the MTS peptide resulted in a gradual increase in the diameter of the MITOPorter, and aggregation occurred when with MTS exceeded 2.5 mol% (Table S1). This tendency 4 corresponded to a previous report showing that it is difficult to maintain envelope-structures in the presence of high densities of the MTS peptide (12). To overcome this problem, we used 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-Mal-PEG (Mal-PEG-DSPE) (Nippon Oil and Fats Co.; Tokyo, Japan) as an anchor between the MTS-peptide and the envelopes of the MITO-Porter.…”
Section: Main Textsupporting
confidence: 90%
“…We previously showed that MTS enhanced the mitochondrial targeting of nanoparticles in cell homogenates (12), however this was not the case, when living cells were used. We conclude that this contradiction was largely the result of the cell environment, where there are many cytoskeletons and a high density of cell components inside the cells.…”
Section: To Evaluate the Mitochondrial Targeting Activity Of The Mts-mentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports showed that the conjugation or direct modification of MTS permitted a macromolecule such as a protein, DNA and a liposomal nanocarrier to be delivered to mitochondria [8][9][10][11][12] . On the other hand, some researchers have reported the use of a mitochondrial RNA aptamer for mitochondrial delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Biolistic methods enable DNA transfer to mitochondria using heavy particles coated with DNA; however, successful delivery has been limited to simple organisms, such as the yeast Saccharomyces cerevisiae [60]. Other strategies for delivery use nanocarriers, such as MITO-Porter, a liposome-based vector used for delivery to the mitochondrial matrix, in a process involving membrane fusion [62]; inclusion of a mitochondrial targeting signal (MTS) peptide with MITO-Porter enhanced mitochondrial delivery [63]. Liposome-like carriers derived from dequalinium (DQAsomes) have been used to deliver a minimitochondrial genome with a GFP gene into the mitochondrial compartment of macrophage cells using GFP fluorescence to monitor delivery [64].…”
Section: Cellular Models Of Mitochondrial Diseasementioning
confidence: 99%